The Bakken Goes Boom: Oil and the Changing Geographies of North Dakota - Caraher, William; Conway, Kyle (Université d'Ottawa | University of Ottawa, 2016)
In 2008, the Bakken went boom. Thanks to advances in hydraulic fracturing, oil production in western North Dakota exploded. As the price of oil went up, so did the oil rigs. People came from all over the country (and the world) in search of work, and cities and towns struggled to keep up. This book is about the challenges they faced. It is about the human dimensions of the boom, as told by artists, poets, journalists, and scholars. It captures the boom at its peak, before the price of oil fell and the boom went bust. This is the only book on the Bakken to bring together such a wide range of voices. It captures a fascinating moment in the history not only of North Dakota, but of global oil production. It sheds light on the impact of oil on local communities that, until now, had not attracted much interest from the outside world. And it shows how North Dakotans, both old and new, have found ways to address the challenges they face in a turbulent, changing environment. With contributions from Carenlee Barkdull, Karin L. Becker, Sebastian Braun, Nikki Berg Burin, Angela Cary, Kyle Cassidy, Heidi Czerwiec, Simon Donato, Rebecca A. Dunham, Julia C. Geigle, John Holmgren, Heather Jackson, Ann Reed, Andrew Reinhard, Richard Rothaus, Melissa Rae Stewart, Jessica Sobolik, Laura Tally, Ryan M. Taylor, Bret A. Weber, Joshua E. Young
Keywords: Oil fields; Social conditions; Economic history; Petroleum industry and trade--Economic aspects; Business cycles; Hydraulic fracturing; North America--Bakken Formation; North Dakota